DIABETOGENIC EFFECT OF STATINS: MOLECULAR MECHANISMS - Arı, Nuray (Universal Journal of Pharmaceutical Research, 2021)
Statins, HMG CoA inhibitors, are potent hypolipidemic drugs.They are used for the prevention of cardiovascular diseases and some of the most commonly used drugs worldwide. Long term statin therapy can cause a modest increase in new-onset diabetes risk, and there is great interest in the mechanisms for this adverse effect. Main proposed mechanisms are increased insulin resistance and some defects in insulin secretion. Many factors can affect the risk including pre-existing diabetic risk, older age and potency of statin. But clearly, the benefits of these drugs in preventing cardiovascular disease outweigh the potential risk of diabetes.The aim of this review is to give underlying pathomechanisms and clinical relevance of diabetogenic effect of statins. Peer Review History: Received: 4 April 2021; Revised: 9 May; Accepted: 13 June; Available online: 15 July 2021 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Dr. Salfarina Ramli , Department of Pharmacology and Pharmaceutical Chemistry, Faculty of Pharmacy, Universiti Teknologi MARA, 42300 Puncak Alam, Selangor, Malaysia. salfarina2892@uitm.edu.my Dr. George Zhu , Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com